Penerapan Model Pembelajaran Kooperatif Tipe Make a Match dan Team Games Tournament terhadap Hasil Belajar - Arie Purwa Kusuma; Ayunitis Khoirunnisa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
This study was conducted to determine whether the results of learning mathematics learners on the material to build a flat quadrilateral taught using Make a Match learning model is better than the TGT learning model. The sample was taken using cluster random sampling. The analysis test is done by normality test and homogeneity test. Normality test using Lilliefors test and Homogeneity test using Fisher test. Hypothesis test using t-test. Based on the calculation concluded the type of Make a Match cooperative learning model and TGT type cooperative learning model come from the normally distributed population. Homogeneity test using Fisher test can be concluded cooperative learning model type Make a Match and cooperative learning model type TGT same or homogeneous. Based on the hypothesis test, Ho is rejected. In conclusion, the result of learning mathematics of learners using Make a Match learning model is better than TGT learning model.